Hubungan Motivasi, Tinggi Badan Dan Power Otot Tungkai Terhadap Keterampilan Bolabasket - Kusuma, Hangga (Media Ilmu Keolahragaan Indonesia, 2016)
Basketball is a sport that is very complex in his game. There are several factors that can relate to and influence the acquisition of skills in basketball. The purpose of this study was to determine the relationship between motivation and contribution, height and leg muscle power the basketball skills. The method used is the correlation method. The subject of the research: high school basketball extracurricular 2 Bae Kudus son, total 50 people. Assessment of motivation on the subject of the inquiry, the measurement of height and leg muscle power as well as basketball skills. From the results of this study concluded that there is a positive and significant relationship between motivation, height and leg muscle power on basketball skills with a contribution of 67%.